Examining Financial Strategy Management: Understanding Financial Performance, Investment Decisions, and Strategic Approaches through Qualitative Description and Literature Review - Molina, Molina; Wilestari, Median (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
This research delves into the complexities of financial strategy management through a qualitative examination and literature review, aiming to illuminate key insights into managing financial performance, investment decisions, and strategic approaches within organizations. The primary objective of this study is to provide a comprehensive understanding of financial strategy management by synthesizing existing knowledge and identifying gaps for further exploration. The research methodology involves a qualitative description and literature review, drawing upon seminal works by renowned scholars in finance, economics, psychology, and strategic management. Findings from the literature review underscore the multifaceted nature of financial strategy management, emphasizing the significance of adopting a balanced and comprehensive approach to financial performance evaluation, integrating both quantitative metrics and qualitative insights. Moreover, the research highlights the pivotal role of investment decisions in driving organizational performance outcomes, elucidating insights from modern portfolio theory, behavioral finance, and empirical studies. Additionally, the study identifies diverse strategic approaches in financial management, ranging from Mintzberg's ten schools of strategy formulation to Porter's competitive strategy frameworks, emphasizing adaptability, innovation, and strategic flexibility in navigating dynamic business environments. The research contributes theoretical insights by enriching existing frameworks and offers practical implications for managerial practice, guiding organizations in enhancing financial management practices and achieving sustainable competitive advantage.